CN108962425A - A kind of preparation method of graphene conductive slurry - Google Patents
A kind of preparation method of graphene conductive slurry Download PDFInfo
- Publication number
- CN108962425A CN108962425A CN201810872994.4A CN201810872994A CN108962425A CN 108962425 A CN108962425 A CN 108962425A CN 201810872994 A CN201810872994 A CN 201810872994A CN 108962425 A CN108962425 A CN 108962425A
- Authority
- CN
- China
- Prior art keywords
- graphene
- graphene oxide
- parts
- mixture
- mixed
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Pending
Links
- OKTJSMMVPCPJKN-UHFFFAOYSA-N Carbon Chemical compound [C] OKTJSMMVPCPJKN-UHFFFAOYSA-N 0.000 title claims abstract description 141
- 229910021389 graphene Inorganic materials 0.000 title claims abstract description 107
- 239000002002 slurry Substances 0.000 title claims abstract description 46
- 238000002360 preparation method Methods 0.000 title claims abstract description 13
- PEDCQBHIVMGVHV-UHFFFAOYSA-N Glycerine Chemical compound OCC(O)CO PEDCQBHIVMGVHV-UHFFFAOYSA-N 0.000 claims abstract description 28
- 239000002270 dispersing agent Substances 0.000 claims abstract description 22
- 239000002904 solvent Substances 0.000 claims abstract description 22
- 239000000945 filler Substances 0.000 claims abstract description 16
- 235000011187 glycerol Nutrition 0.000 claims abstract description 14
- 239000000203 mixture Substances 0.000 claims description 49
- 239000000243 solution Substances 0.000 claims description 23
- XLYOFNOQVPJJNP-UHFFFAOYSA-N water Substances O XLYOFNOQVPJJNP-UHFFFAOYSA-N 0.000 claims description 21
- 239000006185 dispersion Substances 0.000 claims description 20
- LFQSCWFLJHTTHZ-UHFFFAOYSA-N Ethanol Chemical compound CCO LFQSCWFLJHTTHZ-UHFFFAOYSA-N 0.000 claims description 17
- 239000012047 saturated solution Substances 0.000 claims description 17
- NWZSZGALRFJKBT-KNIFDHDWSA-N (2s)-2,6-diaminohexanoic acid;(2s)-2-hydroxybutanedioic acid Chemical compound OC(=O)[C@@H](O)CC(O)=O.NCCCC[C@H](N)C(O)=O NWZSZGALRFJKBT-KNIFDHDWSA-N 0.000 claims description 12
- IKDUDTNKRLTJSI-UHFFFAOYSA-N hydrazine monohydrate Substances O.NN IKDUDTNKRLTJSI-UHFFFAOYSA-N 0.000 claims description 12
- 238000000034 method Methods 0.000 claims description 12
- 238000001914 filtration Methods 0.000 claims description 9
- 238000006243 chemical reaction Methods 0.000 claims description 8
- SQGYOTSLMSWVJD-UHFFFAOYSA-N silver(1+) nitrate Chemical compound [Ag+].[O-]N(=O)=O SQGYOTSLMSWVJD-UHFFFAOYSA-N 0.000 claims description 8
- 238000002156 mixing Methods 0.000 claims description 7
- PNEYBMLMFCGWSK-UHFFFAOYSA-N Alumina Chemical compound [O-2].[O-2].[O-2].[Al+3].[Al+3] PNEYBMLMFCGWSK-UHFFFAOYSA-N 0.000 claims description 6
- QGZKDVFQNNGYKY-UHFFFAOYSA-O Ammonium Chemical compound [NH4+] QGZKDVFQNNGYKY-UHFFFAOYSA-O 0.000 claims description 6
- DKPFZGUDAPQIHT-UHFFFAOYSA-N Butyl acetate Natural products CCCCOC(C)=O DKPFZGUDAPQIHT-UHFFFAOYSA-N 0.000 claims description 6
- 229920001661 Chitosan Polymers 0.000 claims description 6
- PIICEJLVQHRZGT-UHFFFAOYSA-N Ethylenediamine Chemical compound NCCN PIICEJLVQHRZGT-UHFFFAOYSA-N 0.000 claims description 6
- DPXJVFZANSGRMM-UHFFFAOYSA-N acetic acid;2,3,4,5,6-pentahydroxyhexanal;sodium Chemical group [Na].CC(O)=O.OCC(O)C(O)C(O)C(O)C=O DPXJVFZANSGRMM-UHFFFAOYSA-N 0.000 claims description 6
- 239000013078 crystal Substances 0.000 claims description 6
- 239000000706 filtrate Substances 0.000 claims description 6
- 229910002804 graphite Inorganic materials 0.000 claims description 6
- 239000010439 graphite Substances 0.000 claims description 6
- FUZZWVXGSFPDMH-UHFFFAOYSA-N hexanoic acid Chemical group CCCCCC(O)=O FUZZWVXGSFPDMH-UHFFFAOYSA-N 0.000 claims description 6
- 239000007788 liquid Substances 0.000 claims description 6
- 229920000058 polyacrylate Polymers 0.000 claims description 6
- 150000003242 quaternary ammonium salts Chemical class 0.000 claims description 6
- 150000001336 alkenes Chemical class 0.000 claims description 5
- 239000002041 carbon nanotube Substances 0.000 claims description 5
- 229910021393 carbon nanotube Inorganic materials 0.000 claims description 5
- 239000001768 carboxy methyl cellulose Substances 0.000 claims description 5
- 238000007789 sealing Methods 0.000 claims description 5
- 235000019812 sodium carboxymethyl cellulose Nutrition 0.000 claims description 5
- 229920001027 sodium carboxymethylcellulose Polymers 0.000 claims description 5
- XLOMVQKBTHCTTD-UHFFFAOYSA-N Zinc monoxide Chemical group [Zn]=O XLOMVQKBTHCTTD-UHFFFAOYSA-N 0.000 claims description 4
- 238000001556 precipitation Methods 0.000 claims description 4
- 229910001961 silver nitrate Inorganic materials 0.000 claims description 4
- OIFBSDVPJOWBCH-UHFFFAOYSA-N Diethyl carbonate Chemical compound CCOC(=O)OCC OIFBSDVPJOWBCH-UHFFFAOYSA-N 0.000 claims description 3
- 238000003756 stirring Methods 0.000 claims description 3
- QVGXLLKOCUKJST-UHFFFAOYSA-N atomic oxygen Chemical compound [O] QVGXLLKOCUKJST-UHFFFAOYSA-N 0.000 claims description 2
- 238000004108 freeze drying Methods 0.000 claims description 2
- -1 graphite alkene Chemical class 0.000 claims description 2
- 229910052760 oxygen Inorganic materials 0.000 claims description 2
- 239000001301 oxygen Substances 0.000 claims description 2
- XOLBLPGZBRYERU-UHFFFAOYSA-N tin dioxide Chemical compound O=[Sn]=O XOLBLPGZBRYERU-UHFFFAOYSA-N 0.000 claims description 2
- 229910001887 tin oxide Inorganic materials 0.000 claims description 2
- 238000005406 washing Methods 0.000 claims description 2
- 239000011787 zinc oxide Substances 0.000 claims description 2
- CZCSLHYZEQSUNV-UHFFFAOYSA-N [Na].OB(O)O Chemical compound [Na].OB(O)O CZCSLHYZEQSUNV-UHFFFAOYSA-N 0.000 claims 1
- 239000006181 electrochemical material Substances 0.000 abstract description 2
- 239000000463 material Substances 0.000 description 8
- 239000000047 product Substances 0.000 description 8
- 239000012065 filter cake Substances 0.000 description 6
- BQCADISMDOOEFD-UHFFFAOYSA-N Silver Chemical compound [Ag] BQCADISMDOOEFD-UHFFFAOYSA-N 0.000 description 4
- 229960000935 dehydrated alcohol Drugs 0.000 description 4
- 229960004756 ethanol Drugs 0.000 description 4
- 235000019441 ethanol Nutrition 0.000 description 4
- 239000003795 chemical substances by application Substances 0.000 description 3
- 230000000052 comparative effect Effects 0.000 description 3
- 239000011231 conductive filler Substances 0.000 description 3
- 238000001723 curing Methods 0.000 description 3
- 238000001514 detection method Methods 0.000 description 3
- 229920002994 synthetic fiber Polymers 0.000 description 3
- RYGMFSIKBFXOCR-UHFFFAOYSA-N Copper Chemical compound [Cu] RYGMFSIKBFXOCR-UHFFFAOYSA-N 0.000 description 2
- 238000004458 analytical method Methods 0.000 description 2
- 229910052799 carbon Inorganic materials 0.000 description 2
- 239000004020 conductor Substances 0.000 description 2
- 238000011161 development Methods 0.000 description 2
- 230000008595 infiltration Effects 0.000 description 2
- 238000001764 infiltration Methods 0.000 description 2
- 239000002245 particle Substances 0.000 description 2
- 239000000843 powder Substances 0.000 description 2
- 238000005245 sintering Methods 0.000 description 2
- 239000004575 stone Substances 0.000 description 2
- 239000000758 substrate Substances 0.000 description 2
- 238000012360 testing method Methods 0.000 description 2
- 229910000906 Bronze Inorganic materials 0.000 description 1
- GRYLNZFGIOXLOG-UHFFFAOYSA-N Nitric acid Chemical compound O[N+]([O-])=O GRYLNZFGIOXLOG-UHFFFAOYSA-N 0.000 description 1
- 150000003863 ammonium salts Chemical class 0.000 description 1
- 230000009286 beneficial effect Effects 0.000 description 1
- 239000011230 binding agent Substances 0.000 description 1
- 238000009835 boiling Methods 0.000 description 1
- 239000010974 bronze Substances 0.000 description 1
- 229920003123 carboxymethyl cellulose sodium Polymers 0.000 description 1
- 229940063834 carboxymethylcellulose sodium Drugs 0.000 description 1
- 239000000919 ceramic Substances 0.000 description 1
- KUNSUQLRTQLHQQ-UHFFFAOYSA-N copper tin Chemical compound [Cu].[Sn] KUNSUQLRTQLHQQ-UHFFFAOYSA-N 0.000 description 1
- 238000009826 distribution Methods 0.000 description 1
- 230000000694 effects Effects 0.000 description 1
- 238000004100 electronic packaging Methods 0.000 description 1
- 238000005538 encapsulation Methods 0.000 description 1
- 238000013007 heat curing Methods 0.000 description 1
- 238000004519 manufacturing process Methods 0.000 description 1
- 229910052751 metal Inorganic materials 0.000 description 1
- 239000002184 metal Substances 0.000 description 1
- 229910017604 nitric acid Inorganic materials 0.000 description 1
- 238000007781 pre-processing Methods 0.000 description 1
- 238000011160 research Methods 0.000 description 1
- 230000000630 rising effect Effects 0.000 description 1
- 239000000523 sample Substances 0.000 description 1
- 238000011895 specific detection Methods 0.000 description 1
- 239000004094 surface-active agent Substances 0.000 description 1
- 239000002562 thickening agent Substances 0.000 description 1
- 239000013008 thixotropic agent Substances 0.000 description 1
- 238000002604 ultrasonography Methods 0.000 description 1
- 239000010930 yellow gold Substances 0.000 description 1
- 229910001097 yellow gold Inorganic materials 0.000 description 1
Classifications
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01B—CABLES; CONDUCTORS; INSULATORS; SELECTION OF MATERIALS FOR THEIR CONDUCTIVE, INSULATING OR DIELECTRIC PROPERTIES
- H01B1/00—Conductors or conductive bodies characterised by the conductive materials; Selection of materials as conductors
- H01B1/20—Conductive material dispersed in non-conductive organic material
- H01B1/24—Conductive material dispersed in non-conductive organic material the conductive material comprising carbon-silicon compounds, carbon or silicon
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01B—CABLES; CONDUCTORS; INSULATORS; SELECTION OF MATERIALS FOR THEIR CONDUCTIVE, INSULATING OR DIELECTRIC PROPERTIES
- H01B13/00—Apparatus or processes specially adapted for manufacturing conductors or cables
Landscapes
- Engineering & Computer Science (AREA)
- Manufacturing & Machinery (AREA)
- Physics & Mathematics (AREA)
- Chemical & Material Sciences (AREA)
- Dispersion Chemistry (AREA)
- Spectroscopy & Molecular Physics (AREA)
- Conductive Materials (AREA)
- Carbon And Carbon Compounds (AREA)
- Battery Electrode And Active Subsutance (AREA)
Abstract
The invention discloses a kind of preparation methods of graphene conductive slurry, belong to electrochemical material technical field.According to parts by weight, it successively weighs: 30~40 parts of modified graphenes, 50~80 parts of solvents, 10~15 parts of fillers, modified graphene and solvent are mixed in blender by 5~8 parts of dispersing agents, 3~8 parts of glycerine, and filler is sequentially added into blender, dispersing agent and glycerine are 45~55 DEG C in temperature, and revolving speed is under conditions of 800~1000r/min, after being stirred 1~2h, graphene conductive slurry is obtained.The electric conductivity of gained graphene conductive slurry of the invention is effectively improved.
Description
Technical field
The invention discloses a kind of preparation methods of graphene conductive slurry, belong to electrochemical material technical field.
Background technique
With the fast development of electronics and information industry, electric slurry plays important role as its basic material, grinds
Hair novel high-performance, inexpensive electric slurry have become the inexorable trend of current social development.
Electrocondution slurry is the critical material of electronic component encapsulation, electrode and interconnection, mainly includes burning infiltration type electrocondution slurry
With curing type conducting resinl (electrically conductive ink) two major classes.Burning infiltration type electrocondution slurry is used primarily in the industries such as solar battery, after sintering
Make electrode use, curing type electrically conductive ink is widely used in the industries such as printed circuit and Electronic Packaging.Electrocondution slurry is according to it
In filler it is different, carbon slurry (graphite conductor), metal paste (bronze, silver powder, copper powder, yellow gold), Yi Jigai can be divided into
The ceramic slurry of property.Classified according to condition of cure, heat cure, ultra-violet curing etc. can be divided into.
There are many factor for influencing electrocondution slurry electric conductivity, and wherein organic carrier, conductive filler influence maximum to it.Have airborne
Body is the important component of electric slurry, and effect is the carrier for undertaking conductive phase and Binder Phase particle, controls electric slurry
Rheological behavior and initial adhesion to substrate, in order to which electric slurry is printed on substrate.Organic carrier is generally by having
Solvent, thixotropic agent, thickener, surfactant and some other secondary solvent composition.Sieve generation has studied electric slurry use forever
Influence of the boiling characteristics of organic carrier to electrocondution slurry performance, Hao Xiaoguang have studied organic carrier to electric slurry mobility
It influences.In terms of conductive filler, the performance of conductive filler directly affects the performance after electric slurry sintering film forming, is mainly manifested in
Inoxidizability and electric conductivity etc..Wu Cunkun has studied in thick film conductor paste silver powder particle size to the shadow of slurry electric conductivity
It rings, the thunder dawn rising sun is prepared for ultrafine copper powder for electronic paste, it plays important function, Yi Baohua to electric slurry electric conductivity is improved
It is found in the research of carbon composition film potentiometer electrocondution slurry, the size distribution of conductive phase has certain shadow to the electric conductivity of slurry
It rings.The problem of electrocondution slurry traditional at present can not be further increased there is also electric conductivity, therefore also need to study it.
Summary of the invention
The present invention solves the technical problem of: it is asked for what conventional conductive slurry electric conductivity can not further increase
Topic, provides a kind of preparation method of graphene conductive slurry.
In order to solve the above-mentioned technical problem, the technical scheme adopted by the invention is that:
(1) pretreatment graphene oxide dispersion is mixed with ethylenediamine 10:1~30:1 in mass ratio, and pretreatment oxygen is added
The Boratex saturated solution and pretreatment graphene oxide dispersion quality 0.1 that 0.5~0.6 times of quality of graphite alkene dispersion liquid~
0.2 times of carbon nanotube, after ultrasonic disperse, sealing reaction must pre-process graphene oxide mixture, will pre-process graphite oxide
Alkene mixture is mixed with ethanol solution 1:3~1:4 in mass ratio, is filtered, and freeze-drying obtains graphene oxide mixture;
(2) graphene oxide mixture is pulverized and sieved, graphene oxide mixture must be refined, refinement graphene oxide is mixed
Object is mixed with silver nitrate solution 1:10~1:20 in mass ratio, after ultrasonic disperse, must pre-process refinement graphene oxide mixture;
(3) hydrazine hydrate solution is mixed with ammonium polyacrylate 12:1~18:1 in mass ratio, and hydrazine hydrate solution quality 0.3 is added
~0.5 times of pretreatment refines graphene oxide mixture, and after being stirred to react, filtering obtains pre- modified graphene mixture, will be pre-
The washing of modified graphene mixture, it is dry, obtain modified graphene;
(4) according to parts by weight, it successively weighs: 30~40 parts of modified graphenes, 50~80 parts of solvents, 10~15 parts of fillers, 5~
Modified graphene is mixed with solvent, and filler is added by 8 parts of dispersing agents, 3~8 parts of glycerine, dispersing agent and glycerine, stirring
After mixing, graphene conductive slurry is obtained.
Step (1) the pretreatment graphene oxide dispersion is by graphene oxide and water 1:200~1 in mass ratio:
300 mix, and after ultrasonic disperse, 0.5~0.8 times of graphene oxide quality of chitosan quaternary ammonium salt are added, after being stirred to react, obtains pre-
Handle graphene oxide dispersion.
Step (1) the Boratex saturated solution is to heat water to 60 DEG C, and Boratex is added to having crystal precipitation, mistake
Filter, obtains filtrate to get Boratex saturated solution.
Step (4) solvent is butyl acetate, any one in diethyl carbonate or water.
Step (4) filler is zinc oxide, any one in tin oxide or aluminium oxide.
Step (4) dispersing agent is sodium carboxymethylcellulose, any one in dispersing agent NNO or Dispersant MF.
The beneficial effects of the present invention are:
Modified graphene is added when preparing graphene conductive slurry in the present invention, firstly, modified graphene is three-dimensional net structure,
And graphene surface load has chitosan quaternary ammonium salt and ethylenediamine, to make modified graphene in the mistake for forming three-dimensional net structure
Lamellar structure is remained in journey, is not reunited, also, modified graphene is made to possess preferable dispersibility in a solvent, into
And the electric conductivity of product is improved, secondly as graphene is three-dimensional net structure in modified graphene, in preparation process
In, silver powder can be adsorbed in the three-dimensional net structure of modified graphene, so that the electric conductivity of product is further increased, and
And since silver powder is bonded in the network structure of graphene, to can be uniformly distributed in product, no after being added in product
It can occur to reunite or settle, and then further increase the electric conductivity of product, furthermore, due to the chitosan season of graphene surface
Ammonium salt can assign graphene certain charge, to make to generate electrostatic repulsion between graphene, and then can after being added in product
It is further uniformly distributed, further increases the electric conductivity of product.
Specific embodiment
Graphene oxide and water 1:200~1:300 in mass ratio are mixed in ultrasound under conditions of frequency is 45~65kHz
It is poly- to the shell that 0.5~0.8 times of graphene oxide quality is added in the mixture of graphene oxide and water after dispersing 30~40min
Sugared quaternary ammonium salt is 30~50 DEG C in temperature, under conditions of revolving speed is 300~400r/min, after being stirred to react 2~4h, obtains pre- place
Manage graphene oxide dispersion;Pretreatment graphene oxide dispersion and ethylenediamine 10:1~30:1 in mass ratio are mixed in burning
In cup, and the Boratex saturated solution for pre-processing 0.5~0.6 times of graphene oxide dispersion quality and pre- place are added into beaker
The carbon nanotube of 0.1~0.2 times of graphene oxide dispersion quality of reason, the ultrasonic disperse under conditions of frequency is 45~55kHz
After 30~50min, special not synthetic fibre reaction kettle is added in material in beaker, 5~6h of sealing reaction under conditions of being 120 DEG C in temperature
Afterwards, graphene oxide mixture must be pre-processed, the ethyl alcohol that graphene oxide mixture and mass fraction are 20~30% will be pre-processed
Solution 1:3~1:4 in mass ratio mixing is 30~40 DEG C in temperature, and under conditions of revolving speed is 300~400r/min, stirring is mixed
After closing 50~80min, filtering obtains filter cake, filter cake is freeze-dried, obtains graphene oxide mixture;Graphene oxide is mixed
Object crushed 120 meshes, must refine graphene oxide mixture, will refinement graphene oxide mixture and mass fraction be 20~
30% silver nitrate solution 1:10~1:20 in mass ratio mixing, 1~2h of ultrasonic disperse under conditions of frequency is 45~55kHz
Afterwards, refinement graphene oxide mixture must be pre-processed;The hydrazine hydrate solution that mass fraction is 10~12% is pressed with ammonium polyacrylate
Mass ratio 12:1~18:1 is mixed in three-necked flask, and molten with the rate addition hydrazine hydrate of 5~12mL/min in three-necked flask
The pretreatment that 0.3~0.5 times of liquid quality refines graphene oxide mixture, is 55~65 DEG C in temperature, and revolving speed is 300~
Under conditions of 600r/min, after being stirred to react 1~2h, filtering obtains pre- modified graphene mixture, pre- modified graphene is mixed
After object dehydrated alcohol and water successively wash 5~8 times, under conditions of being 60~80 DEG C in temperature after dry 4~6h, modified stone is obtained
Black alkene;According to parts by weight, it successively weighs: 30~40 parts of modified graphenes, 50~80 parts of solvents, 10~15 parts of fillers, 5~8
Modified graphene and solvent are mixed in blender, and sequentially add and fill out into blender by part dispersing agent, 3~8 parts of glycerine
Material, dispersing agent and glycerine are 45~55 DEG C in temperature, under conditions of revolving speed is 800~1000r/min, are stirred 1~2h
Afterwards, graphene conductive slurry is obtained.The Boratex saturated solution is to heat water to 60 DEG C, and Boratex is added to there is crystal analysis
Out, it filters, obtains filtrate to get Boratex saturated solution.The solvent is butyl acetate, any one in diethyl carbonate or water
Kind.The dispersing agent is sodium carboxymethylcellulose, any one in dispersing agent NNO or Dispersant MF.
Graphene oxide and water 1:300 in mass ratio are mixed in ultrasonic disperse 40min under conditions of frequency is 65kHz
Afterwards, into the mixture of graphene oxide and water be added 0.8 times of graphene oxide quality chitosan quaternary ammonium salt, in temperature be 50
DEG C, under conditions of revolving speed is 400r/min, after being stirred to react 4h, obtain pretreatment graphene oxide dispersion;Pretreatment is aoxidized
Graphene dispersing solution and ethylenediamine 30:1 in mass ratio are mixed in beaker, and pretreatment graphene oxide point is added into beaker
0.6 times of dispersion liquid quality of Boratex saturated solution and the carbon nanotube of 0.2 times of graphene oxide dispersion quality of pretreatment, Yu Pin
Rate be 55kHz under conditions of after ultrasonic disperse 50min, special not synthetic fibre reaction kettle is added in material in beaker, in temperature be 120 DEG C
Under the conditions of sealing reaction 6h after, must pre-process graphene oxide mixture, will pretreatment graphene oxide mixture and quality divide
Number mixes for 30% ethanol solution 1:4 in mass ratio, is 40 DEG C in temperature, under conditions of revolving speed is 400r/min, is stirred
After 80min, filtering obtains filter cake, filter cake is freeze-dried, obtains graphene oxide mixture;Graphene oxide mixture is crushed
120 meshes are crossed, graphene oxide mixture must be refined, the nitric acid that graphene oxide mixture and mass fraction are 30% will be refined
Silver-colored solution 1:20 in mass ratio mixing must pre-process refinement graphite oxide under conditions of frequency is 55kHz after ultrasonic disperse 2h
Alkene mixture;The hydrazine hydrate solution that mass fraction is 12% is mixed in three-necked flask with ammonium polyacrylate 18:1 in mass ratio,
And it is mixed in three-necked flask with the pretreatment refinement graphene oxide that the rate of 12mL/min is added 0.5 times of hydrazine hydrate solution quality
Object is 65 DEG C in temperature, and under conditions of revolving speed is 600r/min, after being stirred to react 2h, filtering obtains pre- modified graphene mixing
Object, after pre- modified graphene mixture dehydrated alcohol and water are successively washed 8 times, dry 6h under conditions of being 80 DEG C in temperature
Afterwards, modified graphene is obtained;According to parts by weight, it successively weighs: 40 parts of modified graphenes, 80 parts of solvents, 15 parts of fillers, 8 parts points
Modified graphene and solvent are mixed in blender, and sequentially add filler into blender by powder, 8 parts of glycerine, disperse
Agent and glycerine are 55 DEG C in temperature, under conditions of revolving speed is 1000r/min, after being stirred 2h, obtain graphene conductive slurry
Material.The Boratex saturated solution is to heat water to 60 DEG C, and Boratex is added to there is crystal precipitation, filters, obtains filtrate, i.e.,
Obtain Boratex saturated solution.The solvent is butyl acetate.The dispersing agent is sodium carboxymethylcellulose.
Graphene oxide be crushed into 120 meshes, obtain refinement graphene oxide, by refinement graphene oxide and mass fraction
It mixes for 30% silver nitrate solution 1:20 in mass ratio, under conditions of frequency is 55kHz after ultrasonic disperse 2h, must pre-process
Refine graphene oxide;The hydrazine hydrate solution that mass fraction is 12% is mixed in three mouthfuls with ammonium polyacrylate 18:1 in mass ratio
In flask, and stone is aoxidized with the pretreatment refinement that the rate of 12mL/min is added 0.5 times of hydrazine hydrate solution quality in three-necked flask
Black alkene is 65 DEG C in temperature, and under conditions of revolving speed is 600r/min, after being stirred to react 2h, filtering obtains pre- modified graphene mixing
Object, after pre- modified graphene mixture dehydrated alcohol and water are successively washed 8 times, dry 6h under conditions of being 80 DEG C in temperature
Afterwards, modified graphene is obtained;According to parts by weight, it successively weighs: 40 parts of modified graphenes, 80 parts of solvents, 15 parts of fillers, 8 parts points
Modified graphene and solvent are mixed in blender, and sequentially add filler into blender by powder, 8 parts of glycerine, disperse
Agent and glycerine are 55 DEG C in temperature, under conditions of revolving speed is 1000r/min, after being stirred 2h, obtain graphene conductive slurry
Material.The Boratex saturated solution is to heat water to 60 DEG C, and Boratex is added to there is crystal precipitation, filters, obtains filtrate, i.e.,
Obtain Boratex saturated solution.The solvent is butyl acetate.The dispersing agent is sodium carboxymethylcellulose.
Graphene oxide and water 1:300 in mass ratio are mixed in ultrasonic disperse 40min under conditions of frequency is 65kHz
Afterwards, into the mixture of graphene oxide and water be added 0.8 times of graphene oxide quality chitosan quaternary ammonium salt, in temperature be 50
DEG C, under conditions of revolving speed is 400r/min, after being stirred to react 4h, obtain pretreatment graphene oxide dispersion;Pretreatment is aoxidized
Graphene dispersing solution and ethylenediamine 30:1 in mass ratio are mixed in beaker, and pretreatment graphene oxide point is added into beaker
0.6 times of dispersion liquid quality of Boratex saturated solution and the carbon nanotube of 0.2 times of graphene oxide dispersion quality of pretreatment, Yu Pin
Rate be 55kHz under conditions of after ultrasonic disperse 50min, special not synthetic fibre reaction kettle is added in material in beaker, in temperature be 120 DEG C
Under the conditions of sealing reaction 6h after, must pre-process graphene oxide mixture, will pretreatment graphene oxide mixture and quality divide
Number mixes for 30% ethanol solution 1:4 in mass ratio, is 40 DEG C in temperature, under conditions of revolving speed is 400r/min, is stirred
After 80min, filtering obtains filter cake, filter cake is freeze-dried, obtains graphene oxide mixture;Graphene oxide mixture is crushed
120 meshes are crossed, graphene oxide mixture must be refined;The hydrazine hydrate solution that mass fraction is 12% is pressed into matter with ammonium polyacrylate
Amount is mixed in three-necked flask than 18:1, and is added 0.5 times of hydrazine hydrate solution quality in three-necked flask with the rate of 12mL/min
Refinement graphene oxide mixture, in temperature be 65 DEG C, revolving speed be 600r/min under conditions of, after being stirred to react 2h, filtering,
Obtain pre- modified graphene mixture is in temperature after pre- modified graphene mixture dehydrated alcohol and water are successively washed 8 times
Under conditions of 80 DEG C after dry 6h, modified graphene is obtained;According to parts by weight, successively weigh: 40 parts of modified graphenes, 80 parts molten
Modified graphene and solvent are mixed in blender by agent, 15 parts of fillers, 8 parts of dispersing agents, 8 parts of glycerine, and into blender
Filler, dispersing agent and glycerine are sequentially added, is 55 DEG C in temperature, under conditions of revolving speed is 1000r/min, is stirred 2h
Afterwards, graphene conductive slurry is obtained.The Boratex saturated solution is to heat water to 60 DEG C, and Boratex is added to there is crystal analysis
Out, it filters, obtains filtrate to get Boratex saturated solution.The solvent is butyl acetate.The dispersing agent is carboxymethyl cellulose
Sodium.
Comparative example: the electrocondution slurry of Xiamen graphene Technology Co., Ltd. production.
1 to 3 gained electrocondution slurry of example and comparative example product are subjected to performance detection, the specific detection method is as follows:
The resistivity of above-mentioned electrocondution slurry is tested using four-point probe, specific testing result is as shown in table 1:
Table 1: performance detection table
| Detection content | Example 1 | Example 2 | Example 3 | Comparative example |
| Resistivity/(Ω cm) | 3.53×10-3 | 2.47×10-2 | 9.83×10-3 | 8.34×10-2 |
By 1 testing result of table it is found that the electric conductivity of present invention gained graphene conductive slurry is effectively improved.
Claims (6)
1. a kind of preparation method of graphene conductive slurry, which is characterized in that specific preparation step are as follows:
(1) pretreatment graphene oxide dispersion is mixed with ethylenediamine 10:1~30:1 in mass ratio, and pretreatment oxygen is added
The Boratex saturated solution and pretreatment graphene oxide dispersion quality 0.1 that 0.5~0.6 times of quality of graphite alkene dispersion liquid~
0.2 times of carbon nanotube, after ultrasonic disperse, sealing reaction must pre-process graphene oxide mixture, will pre-process graphite oxide
Alkene mixture is mixed with ethanol solution 1:3~1:4 in mass ratio, is filtered, and freeze-drying obtains graphene oxide mixture;
(2) graphene oxide mixture is pulverized and sieved, graphene oxide mixture must be refined, refinement graphene oxide is mixed
Object is mixed with silver nitrate solution 1:10~1:20 in mass ratio, after ultrasonic disperse, must pre-process refinement graphene oxide mixture;
(3) hydrazine hydrate solution is mixed with ammonium polyacrylate 12:1~18:1 in mass ratio, and hydrazine hydrate solution quality 0.3 is added
~0.5 times of pretreatment refines graphene oxide mixture, and after being stirred to react, filtering obtains pre- modified graphene mixture, will be pre-
The washing of modified graphene mixture, it is dry, obtain modified graphene;
(4) according to parts by weight, it successively weighs: 30~40 parts of modified graphenes, 50~80 parts of solvents, 10~15 parts of fillers, 5~
Modified graphene is mixed with solvent, and filler is added by 8 parts of dispersing agents, 3~8 parts of glycerine, dispersing agent and glycerine, stirring
After mixing, graphene conductive slurry is obtained.
2. a kind of preparation method of graphene conductive slurry according to claim 1, it is characterised in that: step (1) is described
Pretreatment graphene oxide dispersion is to mix graphene oxide with water 1:200~1:300 in mass ratio, after ultrasonic disperse,
0.5~0.8 times of graphene oxide quality of chitosan quaternary ammonium salt is added, after being stirred to react, graphene oxide dispersion must be pre-processed
Liquid.
3. a kind of preparation method of graphene conductive slurry according to claim 1, it is characterised in that: step (1) is described
Boratex saturated solution is to heat water to 60 DEG C, and Boratex is added to there is crystal precipitation, filters, obtains filtrate to get boric acid
Sodium saturated solution.
4. a kind of preparation method of graphene conductive slurry according to claim 1, it is characterised in that: step (4) is described
Solvent is butyl acetate, any one in diethyl carbonate or water.
5. a kind of preparation method of graphene conductive slurry according to claim 1, it is characterised in that: step (4) is described
Filler is zinc oxide, any one in tin oxide or aluminium oxide.
6. a kind of preparation method of graphene conductive slurry according to claim 1, it is characterised in that: step (4) is described
Dispersing agent is sodium carboxymethylcellulose, any one in dispersing agent NNO or Dispersant MF.
Priority Applications (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN201810872994.4A CN108962425A (en) | 2018-08-02 | 2018-08-02 | A kind of preparation method of graphene conductive slurry |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN201810872994.4A CN108962425A (en) | 2018-08-02 | 2018-08-02 | A kind of preparation method of graphene conductive slurry |
Publications (1)
| Publication Number | Publication Date |
|---|---|
| CN108962425A true CN108962425A (en) | 2018-12-07 |
Family
ID=64467219
Family Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| CN201810872994.4A Pending CN108962425A (en) | 2018-08-02 | 2018-08-02 | A kind of preparation method of graphene conductive slurry |
Country Status (1)
| Country | Link |
|---|---|
| CN (1) | CN108962425A (en) |
Cited By (6)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN109811382A (en) * | 2019-03-28 | 2019-05-28 | 烟台恒诺新材料有限公司 | A kind of application of graphene oxide conductive paste in black holesization is directly electroplated |
| CN114068065A (en) * | 2021-03-10 | 2022-02-18 | 杭州安誉科技有限公司 | Conductive material for temperature sensor and use thereof |
| CN114155991A (en) * | 2021-11-05 | 2022-03-08 | 云南巨晶新材料有限公司 | A kind of silver paste graphene composite conductive paste for transparent display screen |
| CN115732117A (en) * | 2022-03-08 | 2023-03-03 | 重庆恩辰新材料科技有限责任公司 | Conductive silver paste for ceramic surface circuit printing and preparation method and application thereof |
| CN115968065A (en) * | 2023-01-13 | 2023-04-14 | 广东骏丰频谱股份有限公司 | Electric heating slurry and preparation method thereof |
| CN116177939A (en) * | 2023-02-23 | 2023-05-30 | 深圳市东大洋水泥制品有限公司 | Anti-freezing concrete and preparation method thereof |
Citations (4)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN105514066A (en) * | 2016-01-19 | 2016-04-20 | 合肥微晶材料科技有限公司 | Composite graphene infrared radiation and heat conduction film and manufacturing method thereof |
| CN106205776A (en) * | 2016-08-14 | 2016-12-07 | 浙江亚通焊材有限公司 | Low temperature curing type Graphene/conductive silver slurry and its preparation method and application |
| CN106469582A (en) * | 2015-08-18 | 2017-03-01 | 中国科学院上海微系统与信息技术研究所 | A kind of electrocondution slurry of graphene-containing and preparation method thereof |
| CN106861617A (en) * | 2017-01-25 | 2017-06-20 | 河北大学 | A kind of preparation method and applications of Graphene/carbon nanotube composite material |
-
2018
- 2018-08-02 CN CN201810872994.4A patent/CN108962425A/en active Pending
Patent Citations (4)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN106469582A (en) * | 2015-08-18 | 2017-03-01 | 中国科学院上海微系统与信息技术研究所 | A kind of electrocondution slurry of graphene-containing and preparation method thereof |
| CN105514066A (en) * | 2016-01-19 | 2016-04-20 | 合肥微晶材料科技有限公司 | Composite graphene infrared radiation and heat conduction film and manufacturing method thereof |
| CN106205776A (en) * | 2016-08-14 | 2016-12-07 | 浙江亚通焊材有限公司 | Low temperature curing type Graphene/conductive silver slurry and its preparation method and application |
| CN106861617A (en) * | 2017-01-25 | 2017-06-20 | 河北大学 | A kind of preparation method and applications of Graphene/carbon nanotube composite material |
Cited By (8)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN109811382A (en) * | 2019-03-28 | 2019-05-28 | 烟台恒诺新材料有限公司 | A kind of application of graphene oxide conductive paste in black holesization is directly electroplated |
| CN109811382B (en) * | 2019-03-28 | 2021-04-20 | 烟台恒诺新材料有限公司 | Application of graphene oxide conductive paste in black hole direct electroplating |
| CN114068065A (en) * | 2021-03-10 | 2022-02-18 | 杭州安誉科技有限公司 | Conductive material for temperature sensor and use thereof |
| CN114155991A (en) * | 2021-11-05 | 2022-03-08 | 云南巨晶新材料有限公司 | A kind of silver paste graphene composite conductive paste for transparent display screen |
| CN115732117A (en) * | 2022-03-08 | 2023-03-03 | 重庆恩辰新材料科技有限责任公司 | Conductive silver paste for ceramic surface circuit printing and preparation method and application thereof |
| CN115732117B (en) * | 2022-03-08 | 2024-01-19 | 重庆恩辰新材料科技有限责任公司 | Conductive silver paste for ceramic surface circuit printing and preparation method and application thereof |
| CN115968065A (en) * | 2023-01-13 | 2023-04-14 | 广东骏丰频谱股份有限公司 | Electric heating slurry and preparation method thereof |
| CN116177939A (en) * | 2023-02-23 | 2023-05-30 | 深圳市东大洋水泥制品有限公司 | Anti-freezing concrete and preparation method thereof |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| CN101620893B (en) | All-silver electronic paste and preparation method thereof | |
| CN101271929B (en) | Leadless solar battery silver paste and method for producing the same | |
| CN105345012B (en) | A kind of preparation method and application of high conductivity flake silver powder | |
| CN102592710B (en) | Solar energy battery electrode-conducting silver slurry containing micron-size mixed silver powders | |
| CN108133768A (en) | A kind of high conductivity low temperature curing type electrocondution slurry and preparation method thereof | |
| CN102311714B (en) | High thermal and electric conducting adhesive filled with nanometer silver and preparation method thereof | |
| CN101271928A (en) | High-viscosity solar cell front silver paste and preparation method thereof | |
| WO2024217073A1 (en) | Silver-copper composite conductive paste capable of being sintered at low temperature, method for preparing same and use thereof | |
| CN108770194A (en) | The preparation method of conductive silver paste used for printed circuit | |
| CN106128555A (en) | A kind of high connductivity crystal silicon solar batteries front electrode silver slurry and preparation method thereof | |
| CN105802346B (en) | A kind of composite conducting ink film and preparation method thereof | |
| CN102097183A (en) | Process for preparing conductive slurry for crystalline silicon solar cell front electrode | |
| CN112820440A (en) | High-conductivity conductive silver paste and preparation method thereof | |
| CN108597676B (en) | A preparation method and application of low-temperature solidified silver paste containing organic bentonite | |
| CN111748191A (en) | Two-dimensional graphene composite material with copper nanoparticles supported on the surface, preparation method and application thereof | |
| CN109401442A (en) | A kind of silver-plated electrically conductive ink of UV curing nano and preparation method thereof | |
| JP7093812B2 (en) | Silver powder and its manufacturing method | |
| CN105304161A (en) | Low-temperature environment-friendly conductive silver paste and preparation method and application thereof | |
| CN102103895B (en) | Silver paste used for positive electrodes of solar batteries and grid lines, preparation method thereof and solar battery containing same | |
| CN109822107B (en) | A kind of preparation method of gold nanoparticle composite biomass carbon material | |
| CN107910132A (en) | A kind of preparation method of high dispersive type electrocondution slurry | |
| CN107331438A (en) | A kind of environment protection solar cell front electrode conductor paste and preparation method thereof | |
| CN113284672B (en) | Preparation method of silver nanowire conductive paste | |
| CN106830691B (en) | A kind of glass powder for graphene-doped electronic paste and preparation method thereof | |
| CN106601334A (en) | Electronic paste for touch screens and preparation method thereof |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| PB01 | Publication | ||
| PB01 | Publication | ||
| SE01 | Entry into force of request for substantive examination | ||
| SE01 | Entry into force of request for substantive examination | ||
| RJ01 | Rejection of invention patent application after publication |
Application publication date: 20181207 |
|
| RJ01 | Rejection of invention patent application after publication |